Coupling imaging mass cytometry with Alcian blue histochemical staining for a single-slide approach - Hemon, Patrice; Ben-Guigui, Danivanh; Geier, Margaux; Castillon, Marine; Paranthoen, Corentin; Pers, Jacques-Olivier; Le Rochais, Marion; Uguen, Arnaud (Frontiers in Immunology, 2024)
Imaging mass cytometry (IMC) is a metals-mass spectrometry-based method allowing highlymultiplex immunophenotyping of cells within tissue samples. Some limitations of IMC are nevertheless its 1 µm resolution and its time and costs of analysis limiting respectively the detailed histopathological analysis of IMC-produced images as well as its application to small selected tissue regions of interest (ROI) of one to few squared-millimeters. Coupling on a single tissue section IMC and histopathological analyses could permit a better selection of the ROI for IMC analysis as well as co-analysis of immunophenotyping and histopathological data until the single-cell level. The development of this method is the aim of the present study in which we point to the feasibility of applying the IMC process to tissue sections previously alcian blue-stained and digitalized before IMC tissue destructive analyses. This method could help to improve the process of IMC in terms of ROI selection, time of analysis as well as the confrontation between histopathological and immunophenotypic data of cells.